Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/ncomms5837
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Stranski–Krastanov growth at the initial stage of atmospheric water condensation

Abstract: The precipitation products (rain, snow and so on) of atmospheric water vapour are widely prevalent, and yet the map of its initial stage at a surface is still unclear. Here we investigate the condensation of water vapour occurring in both the hydrophobic-hydrophilic interface (graphene/mica) and the hydrophilic-hydrophilic interface (MoS 2 /mica) by in situ thermally controlled atomic force microscopy. By monitoring the dynamic dewetting/rewetting transitions process, the ice-like water adlayers, at the hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 34 publications
8
92
0
2
Order By: Relevance
“…For example, water molecules can intercalate under the graphene or MoS 2 layers covering hydrophilic substrates. This confined water layer was found to significantly enlarge friction at graphene or MoS 2 surfaces [146][147][148][149][150]. The enhancement of friction by intercalated water can be primarily attributed to the activation of graphene flexural modes and the high frequency modes involving O-H vibrations which effectively promote energy transfer to the substrate.…”
Section: Perspectivesmentioning
confidence: 95%
“…For example, water molecules can intercalate under the graphene or MoS 2 layers covering hydrophilic substrates. This confined water layer was found to significantly enlarge friction at graphene or MoS 2 surfaces [146][147][148][149][150]. The enhancement of friction by intercalated water can be primarily attributed to the activation of graphene flexural modes and the high frequency modes involving O-H vibrations which effectively promote energy transfer to the substrate.…”
Section: Perspectivesmentioning
confidence: 95%
“…First, that water layers coated by graphene still interact with water molecules on the environment because water molecules can adsorb and desorb through graphene edges and cracks [57,58]. That implies that processes of wetting and dewetting can happen below the graphene layer depending on environmental [59,60] and temperature conditions [61]. This fact has been used to study also the evolution of water films between a substrate and graphene as a function of temperature.…”
Section: Graphene Templatementioning
confidence: 99%
“…Recently, graphene has been employed to encapsulate objects such as single yeast cells [31], bacteria [32], water molecules [33][34][35][36][37][38][39][40][41][42], fluorescent films [43], single-stranded DNA and DNA nanostructures [44,45]. It was demonstrated that graphene replicates the topography of the DNA molecules [44,45].…”
Section: Introductionmentioning
confidence: 99%